Thermodynamic properties of the two-dimensional Heisenberg antiferromagnetic model on kagome lattice. (15th February 2023) - Lima, L.S.
Abstract: Thermodynamic quantities as entropy and specific heat that are of evident interest, are obtained for the nearest-neighbor antiferromagnetic Heisenberg model on kagome lattice using the linear spin-wave approach. The results are obtained for different extensions of the model with single-ion anisotropy and out-of-plane Dzyaloshinskii–Moriya (DMI) interaction. We obtain the entropy as a function of the DMI interaction, single-ion anisotropy strength and anisotropy with aim to verify the effect of these corrections that occurs in real magnetic materials on entropy and specific heat. Furthermore, we obtain the specific heat as a function of temperature T and found a discontinuity in the range of large T indicating so, a phase transition in this range of temperature. Highlights: The entropy and specific heat as a function of T and parameters of the system are calculated using the spin wave approach. The specific heat is analyzed at limit of high-temperature and low-temperature. The behavior of specific heat at high-temperature is analyzed.